PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN KAHOOT UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS X PADA MATA PELAJARAN MATEMATIKA - Adillah Resfia El Wa'fa; Dwi Sulistyaningsih; Sri Haryanti (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2024)
Mathematics learning often poses challenges due to low student interest, resulting in reduced participation and outcomes. This study aims to enhance students' learning interest through the application of Problem-Based Learning (PBL) assisted by Kahoot. Using a Classroom Action Research (CAR) approach, the study was conducted in two cycles, each comprising planning, implementation, observation, and reflection. Results showed an increase in students' learning interest from 51% (low) in the pre-cycle to 67% (moderate) in Cycle I, and 81% (high) in Cycle II. The findings demonstrate the effectiveness of PBL assisted by Kahoot in fostering interest and engagement in mathematics. Teachers are encouraged to integrate gamified tools like Kahoot and tailor learning strategies to students' needs.